Sensitivity analysis of three-wheel vehicle's suspension parameters influencing ride behavior. (July 2018) - Sharma, Rakesh Chandmal; Sharma, Sunil Kumar
In this article coupled vertical–lateral 9 degree-of-freedom model of a three-wheel vehicle formulated using Lagrangian dynamics is presented in order to determine its vertical and lateral ride. The model is justified by correlating the power spectral density vertical and lateral acceleration results determined from analysis with the same obtained from experimental measurements. The ride comfort of the vehicle is evaluated on the basis of ISO 2631-1 criteria. The sensitivity of vehicle suspension parameters on vertical and lateral ride behavior is analyzed, and it is noticed that rear-suspension damping coefficient, front-tire stiffness, rear-tire stiffness, front-tire damping coefficient, and rear-tire damping coefficient are critical parameters for vertical power spectral density acceleration. Rear-suspension stiffness, rear-suspension damping coefficient, front-tire stiffness, and rear-tire stiffness are critical parameters for lateral power spectral density acceleration.